Actinomycosis of the Tongue: A Case Report and Review of Literature - Fiorella D'Amore; Roberto Franchini; Laura Moneghini; Niccolò Lombardi; Giovanni Lodi; Andrea Sardella; Elena M. Varoni (MDPI AG, 2020)
Background: Actinomycosis of the tongue is an uncommon, suppurative infection of lingual mucosa, caused by actinomyces. The clinical diagnosis may present serious difficulties because of its ability to mimic other lesions, including both benign and malignant neoplasms. Methods: Here, we describe the case of a 52-years-old patient affected by an asymptomatic, tumor-like tongue swelling, then diagnosed as actinomycosis. A review of tongue localization of actinomycosis is also reported, with emphasis on clinical findings and therapy. Results and Conclusion: Early diagnosis and treatment, with pus drainage and systemic antibiotic therapy, are pivotal to avoid severe and life-threatening complications.